What are the "four roots of capacity and nature"? - CHAN, Alan Kam Leung (Institutional Knowledge at Singapore Management University, 2004)
During the third century C.E., a debate on the relationship between “capacity” (cai 才) and “nature” (xing 性) captured the imagination of the Chinese elite. Historical sources relate that four views were put forward on the subject, which continued to dominate the intellectual scene during the fourth and fifth centuries. Yin Hao 殷 浩 (306–356), a major statesman and leader of the literati, for example, was known especially for his expertise on the four views of “capacity and nature” (caixing) (Shishuo xinyu 1992, 4.34; cf. Mather 1976, 110).1 Writing in the fifth century, Wang Sengqian 王 僧 虔 (426–485) observed that caixing was basic to the repertoire of every learned speaker in philosophical debates; that is to say, no intellectual worthy of the name could afford not to know or be able to say something about it.2 There is little question that the debate on caixing occupied a privileged position in early medieval Chinese philosophy. It is not entirely clear, however, what the arguments were.